2017
DOI: 10.1093/pcp/pcx039
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Analysis of Developmental Reprogramming in Protoplasts of the Moss Physcomitrella patens

Abstract: The moss Physcomitrella patens is a model system for studying Plant developmental processes. To better understand the biochemical and physiological changes involved in developmental reprogramming, we conducted a quantitative proteomics analysis for protonemata, protoplasts made therefrom and protoplasts regenerated for 2 d. Using an iTRAQ peptide labeling strategy and liquid chromatography-tandem mass spectrometry (LC-MS/MS), >3,000 peptides and 1,000 proteins were quantified. Of these, 162 proteins were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…The expression pattern of PpBBE1 reflects the differences in the two protonema tissue types, being highly expressed in chloronema, but not detectable in caulonema. This finding nicely correlates with the recently performed transcriptome analysis of protoplasts [35] as well as of chloronema cells [10,11] that have shown a significant upregulation of carbohydrate and energy metabolism in these early stages of the plant's life cycle. Our hypothesis that PpBBE is involved in carbohydrate degradation is further supported by the fact that also fungi use cellobiose for energy production, which is initially metabolized extracellularly to cellobionic acid and then further degraded by cellobionic acid phosphorylases after transport into the cytoplasm.…”
Section: Discussionsupporting
confidence: 87%
“…The expression pattern of PpBBE1 reflects the differences in the two protonema tissue types, being highly expressed in chloronema, but not detectable in caulonema. This finding nicely correlates with the recently performed transcriptome analysis of protoplasts [35] as well as of chloronema cells [10,11] that have shown a significant upregulation of carbohydrate and energy metabolism in these early stages of the plant's life cycle. Our hypothesis that PpBBE is involved in carbohydrate degradation is further supported by the fact that also fungi use cellobiose for energy production, which is initially metabolized extracellularly to cellobionic acid and then further degraded by cellobionic acid phosphorylases after transport into the cytoplasm.…”
Section: Discussionsupporting
confidence: 87%
“…Transcriptomic studies investigating Arabidopsis protoplast regeneration have shown that protoplasts undergoing dedifferentiation display gene expression profiles resembling those associated with stress responses and stress-associated cellular senescence (21,24). Similar trends are also observed in Physcomitrella patens protoplasts (133,137). Cellular oxidative stress is transiently elevated upon isolation of protoplasts, and ROS levels are several-fold higher within 1 day after protoplast isolation (127).…”
Section: Protoplast Regenerationmentioning
confidence: 72%
“…A first conclusion of these studies is that the overall 3D interaction network within the Arabidopsis nucleus resembles that of Drosophila and mammalian cells [69] and reveals distinct types of interactions between chromatin states [70]. This is particularly striking for the separation between euchromatin and heterochromatin [64].…”
Section: Genome Topographymentioning
confidence: 99%